The variation of load diffusion and ballast bed deformation with loading condition: an experiment study. Issue 2 (4th March 2022) - Fu, Longlong; Tian, Zhekan; Zheng, Yuexiao; Ye, Weitao; Zhou, Shunhua
ABSTRACT: Ballast bed deformation is significantly influenced by its internal stress state. However, investigations concerning ballast bed deformation focus mainly on the deformation behaviour under various external loading conditions or ballast states, where the influence of load diffusion variation has rarely been considered directly. In this work, a full-scale model test was established to obtain simultaneously the external deformation and the internal stress of ballast bed, with respect to various loading conditions (equivalent axle load 14–30 t, 3–6 Hz). The results show that both average stress and stress ratio on ballast increase with loading magnitude. Meanwhile, a larger proportion of vertical load concentrates within the sleeper projection area. Accordingly, the plastic (elastic) deformation is more (less) sensitive to the load variation at larger wheel–rail load. Besides, the dynamic stiffness increases gradually with loading amplitude while showing a small drop as loading frequency increases.